Synthesis and characterization of a sol-gel derived ureasilicate hybrid organic-inorganic matrix containing CdS colloidal particles - Boev, Victor Ivanov (2004)
A hybrid organic-inorganic material filled with in situ generated inorganic particles has been synthesised by the homogeneous precipitation of CdS from aqueous solutions of Cd(NO3)2 and CH3CSNH2 . These highly transparent, homogeneous and flexible CdS doped xerogels were prepared by the sol-gel technique using, as precursors, organically modified silicon alkoxide (3-isocyanatepropyltriethoxysilane) and a di-amine functionalized oligopolyoxyethylene (Jeffamine ED-600), which by subsequent hydrolysis and condensation processes formed a solid 3-D network. TEM studies indicate the presence of round nanoparticles around 20 nm in diameter dispersed in a homogeneous amorphous matrix. The samples were also characterized by spectroscopic (UV-visible and photoluminescence) and XRD techniques.